Prisoner Transfer Within the Irish-UK Common Travel Area (CTA) After Brexit: Human Rights Between Politics and Penal Reform. (April 2021) - Wilson, Tim J
The UK Government proposed in February 2020 that sentenced prisoner transfers with EU member states should continue after Brexit, but using a more 'effective' process than the existing CoE convention. The article analyses, with a particular focus on the Irish-UK CTA, the significance of continued UK human rights compliance for the achievement of this objective and the interrelationship of this issue with extradition/surrender (including the surrender of fugitive prisoners). It is concluded that Brexit has most probably raised the level of formal and institutional human rights compliance (including legal aid/assistance and the direct enforcement of prisoners' rights in domestic courts) required from the UK for criminal justice cooperation with EU member states. Entering into such undertakings would not assist criminal impunity or the evasion of lawfully imposed penalties. Such undertakings, however, cannot help to resolve many problems inherent in prisoner transfer within the EU. The creation of a truly effective and rehabilitative transfer system would require (a) constructive UK Government participation in inter-governmental (including the UK devolved governments)/EU arrangements capable of incrementally resolving or effectively mitigating criminal justice cooperation problems and (b) acceptance at Westminster that this aspect of post-Brexit readjustment is likely to be intermittent and of long-duration.